BALLO+BALLO. - Toscani Ballo, Marirosa (Milano : Silvana Editoriale, 2009)
On the occasion of the 48th edition of the Salone del Mobile 2009, the Contemporary Art Pavillion in Milan hosted a major exhibition on the work of Aldo Ballo and Marirosa Toscani Ballo, which traced the history of Italian design through images of the objects and their creators.The photography studio created by Aldo and Marirosa Toscani Ballo in the Fifties has been a focal point for the most important designers in the most fascinating period for international design.The manner in which the Ballo atelier set about taking photographs created a new school: a photography which, in search of a pure image, is able to "enter inside the objects", as Aldo Ballo himself used to say.The catalogue, with many critical essays and illustrations, tells the story of a laboratory for producing images, which marked the history of design.
Il linguaggio dell'oggetto attraverso le fotografie di Aldo Ballo e Marirosa Toscani Ballo; The language of the object through the photos of Aldo Ballo and Marirosa Toscani Ballo.
Engels
Italiaans
boek
Keywords: Ballo, Aldo; Toscani Ballo, Marirosa; Italië